Evaluation of a Three-Dimensional Stereophotogrammetric Method to Identify and Measure the Palatal Surface Area in Children with Unilateral Cleft Lip and Palate. (January 2016) - De Menezes, Marcio; Cerón-Zapata, Ana Maria; López-Palacio, Ana Maria; Mapelli, Andrea; Pisoni, Luca; Sforza, Chiarella
Objective: To assess a three-dimensional (3D) stereophotogrammetric method for area delimitation and evaluation of the dental arches of children with unilateral cleft lip and palate (UCLP). Obtained data were also used to assess the 3D changes occurring in the maxillary arch with the use of orthopedic therapy prior to rhinocheiloplasty and before the first year of life. Design: Within the collaboration between the Università degli Studi di Milano (Italy) and the University CES of Medellin (Colombia), 96 palatal cast models obtained from neonatal patients with UCLP were analyzed using a 3D stereophotogrammetric imaging system. Main Outcome Measures: The area of the minor and greater cleft segments on the digital dental cast surface were delineated by the visualization tool of the stereophotogrammetric software and then examined. "Trueness" of the measurements, as well as systematic and random errors between operators' tracings ("precision") were calculated. Results: The method gave area measurements close to true values (errors lower than 2%), without systematic measurement errors for tracings by both interoperators and intraoperators ( P > .05). Statistically significant differences ( P < .05) were noted for alveolar segment and time. Conclusions: Maxillary segments have the potential for growth during presurgical orthopedic treatment in the early neonatal period. The cleft segment delimitation on digital dental casts and area measurements by the 3D stereophotogrammetric system revealed an accurate (true and precise) method for evaluating the stone casts of newborn patients with UCLP.